Underlying Mechanisms of Tai-Chi-Chuan Training for Improving Balance Ability in the Elders - 郭蓝远 杨照彬 尤玉琳 陈胜凯 杨志鸿 侯易佑 吴汶兰 (Chinese journal of integrative medicine, 2014)
Objective： To compare balance ability between elderly individuals who practiced Tai-Chi-Chuan （TCC） for average 9.64 years and elderly individuals who did not practice TCC and its relationship with lower extremity muscle strength and ankle proprioception. Methods： Twenty-five elderly volunteers were divided into two groups according to their TCC practcing experience. Sixteen were TCC group and the other nine were control population. Subjects completed a static balance test and ankle proprioception test using a custom-designed evaluation system, and concentric and eccentric knee extensor and flexor muscle strength tests. Subjects stood on the plate form to measure the proprioception in functional standing position which was differed from the previous studies. Multiple linear regressions were also used to predict the important factor affecting balance. Results： TCC group performed better than the control group in balance, proprioception, and muscle strength of lower extremity. The proprioception was the most important factor related to balance ability and it can be accounted for explaining 44% of variance in medial-lateral sway direction, and 53% of variance in antero-posterior sway direction. The proprioception may be a more important factor which affecting the balance ability. Conclusion： TCC training is recommended to the elders; as it can improve balance ability through better proprioception.